Interlegality of Matrimonial Property Law: Exploring the Dynamics of Property Distribution in West Sumatra - Embrizal Embrizal; Fauzan Fauzan (Yayasan Lembaga Studi Makwa, 2026)
This study explores the interlegality of matrimonial property law in West Sumatra by examining the interaction between Islamic law, Minangkabau customary law, and judicial practice in the distribution of matrimonial property, particularly buildings constructed on harta pusaka tinggi (matrilineal ancestral property). It aims to analyze judicial reasoning in resolving such disputes and assess whether judicial decisions reflect substantive justice within Indonesia’s plural legal system. This research employs a normative legal method using statutory, conceptual, case, and comparative approaches. Primary sources consist of Religious Court decisions on matrimonial property disputes, while secondary sources include legislation, Islamic legal doctrines, customary law principles, and relevant scholarly literature. The findings show that disputes involving harta pusaka tinggi demonstrate interlegality, where Islamic law, customary law, and state law interact in judicial decision-making. Courts distinguish communal ownership of customary inherited land from buildings acquired during marriage, recognizing the latter as matrimonial property while preserving the customary status of ancestral land. This approach balances legal certainty, customary values, and the rights of both spouses without undermining communal ownership. The study concludes that the dynamics of matrimonial property distribution in West Sumatra are shaped by interlegal processes that harmonize Islamic law, customary law, and judicial discretion to achieve substantive justice. Academically, this research contributes to Islamic family law by advancing interlegality as an analytical framework for resolving matrimonial property disputes in plural legal systems and providing a conceptual reference for future comparative legal studies and judicial practice.